2016
DOI: 10.1002/ep.12431
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of naphthalenesulfonic acids using wild almond shell activated carbon from aqueous solution

Abstract: Activated carbon was prepared from wild almond shells using phosphoric acid as an activating agent. The BET surface area and the pore volume were found to be 1133.25 m2/g and 1.41 cm3/g, respectively. Batch adsorption of two naphthalene dye intermediates, H‐ and γ‐acid was carried out using prepared activated carbon. The maximum adsorption capacities were found to be 911 and 809.4 mg/g, respectively, at 65°C. Freundlich isotherm fitted well the equilibrium data, indicating favorable adsorption of both the acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…Besides, only a peak at 398.85 eV is found in N 1s of Figure d. After sorption, the N 1s spectrum can be decomposed in two distinguishable peaks centered at 398.9 and 401.35 eV, which are earmarked to pyridine nitrogen and protonated pyridyl group, respectively. , The affinity of NSA for the resin may occur through electrostatic interactions, and similar results were previously reported for the sorption of aromatic sulfonic acids. , Depending on the XPS analysis, the proposed sorption mechanism can be elucidated by the synergistic effect of electrostatic attraction and π–π stacking.…”
Section: Resultssupporting
confidence: 68%
“…Besides, only a peak at 398.85 eV is found in N 1s of Figure d. After sorption, the N 1s spectrum can be decomposed in two distinguishable peaks centered at 398.9 and 401.35 eV, which are earmarked to pyridine nitrogen and protonated pyridyl group, respectively. , The affinity of NSA for the resin may occur through electrostatic interactions, and similar results were previously reported for the sorption of aromatic sulfonic acids. , Depending on the XPS analysis, the proposed sorption mechanism can be elucidated by the synergistic effect of electrostatic attraction and π–π stacking.…”
Section: Resultssupporting
confidence: 68%
“…22 Biomass activation is a well-established method for obtaining porous adsorbent materials. Thitame et al 23 have recently reported the use of phosphoric acid as an activating agent to produce activated carbon from wild almond shell. The maximum adsorption capacity of the resulting material is 911 mg g −1 .…”
Section: Physical Methodsmentioning
confidence: 99%
“…1,2 The dye wastewater produced by many industries, such as textile, plastic, clothing, leather, food processing, etc., contains a large number of organic dyes. 3,4 Dye wastewater has a high organic pollutant content and complex composition, exhibits resistance to photolysis and oxidation, and contains a variety of biotoxic or carcinogenic, teratogenic or mutagenic organic substances, which are extremely harmful to the environment. 5 In particular, methylene blue (MB) is applied for a wide range of applications, such as chemical indicators, dyes, biological stains, and drugs, due to its exceptional staining effect and reducibility.…”
Section: Introductionmentioning
confidence: 99%